CONTRADICTION IN HADITHS REGARDING PRAYING ON A CONVEYANCE - Shobri, Alwi (Nabawi: Journal of Hadith Studies, 2024)
Two hadiths appear contradictory regarding the permissibility of praying in a conveyance. One hadith indicates that its permissibility is only limited to sunnah prayers and another hadith allows for obligatory prayers. This contradiction has the potential to cause doubt and confusion for Muslims. Prayer is one of the fundamental acts of worship, the implementation of which is as far as possible accompanied by in-depth knowledge of the correct rules and procedures. This research aims to resolve the problems that arise from these hadith contradictions using the study of Mukhtalif al-ḥadīṡ's science. The method used is library research with a descriptive-analytical approach. Hadith sources used as references include Ṣaḥīḥ al-Bukhārī, Ṣaḥīḥ Muslim, Sunan Abū Dāwud, Sunan Tirmidhī, and Musnad Aḥmad ibn Ḥanbal. The analysis was carried out by studying aḥwāl al-ḥadīṡ and applying the scientific method of mukhtalif al-ḥadīṡ. The research results show that the al-jam` al-tawfīq method with correlative understanding can be used to compromise these two hadiths. With this method, it is known that praying on a vehicle is only permissible for sunnah prayers. For obligatory prayers, this is permissible only when there is a syar'i reason which causes a person to be unable to get out of the vehicle to perform the prayer completely. [Terdapat dua hadis yang tampak kontradiktif mengenai kebolehan salat di atas kendaraan. Satu hadis mengindikasikan bahwa kebolehannya hanya terbatas pada salat sunnah dan hadis lain memperbolehkan untuk salat wajib. Kontradiksi itu berpotensi menimbulkan keraguan dan kebingungan bagi umat Islam. Padahal salat adalah salah satu ibadah fundamental yang pelaksanaannya sebisa mungkin disertai dengan pengetahuan mendalam mengenai aturan dan tata cara yang benar. Penelitian ini bertujuan menyelesaikan permasalahan yang muncul dari kontradiksi hadis tersebut menggunakan kajian ilmu mukhtalif al-ḥadīṡ. Metode yang digunakan adalah penelitian kepustakaan (library research) dengan pendekatan deskriptif-analitis. Sumber-sumber hadis yang dijadikan rujukan meliputi Ṣaḥīḥ al-Bukhārī, Ṣaḥīḥ Muslim, Sunan Abū Dāwud, Sunan Tirmidhī, dan Musnad Aḥmad ibn Ḥanbal. Analisis dilakukan dengan mengkaji aḥwāl al-ḥadīṡ dan menerapkan metode ilmu mukhtalif al-ḥadīṡ. Hasil penelitian menunjukkan bahwa metode al-jam` al-tawfīq dengan pemahaman korelatif dapat digunakan untuk mengompromikan dua hadis tersebut. Dengan metode itu, diketahui bahwa pada dasarnya salat di atas kendaraan hanya dibolehkan untuk salat sunah. Untuk salat wajib, kebolehannya hanya ketika terdapat uzur syar'i yang menyebabkan seseorang tidak bisa turun dari kendaraan untuk melaksanakan salat secara sempurna.]